Implementasi Kepemimpinan Kearifan Lokal Bugis pada Manajemen Berbasis Sekolah di Kabupaten Bone - Dwiyama, Fajri (Jurusan Tarbiyah STAI Al-Gazali Bone, 2024)
This study examines the implementation of Bugis local wisdom leadership values in the context of school-based management (SBM) in Bone Regency, South Sulawesi. The local wisdom of Bugis which is reflected in the concept of